2021
DOI: 10.1161/jaha.120.019671
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Influenza Vaccine Uptake in Patients With Cardiovascular Disease and Strategies for Improvement

Abstract: Cardiovascular disease (CVD) is the leading cause of death and disability worldwide. Influenza infection is associated with an increased risk of cardiovascular events (myocardial infarction, stroke, and heart failure exacerbation) and mortality, and all‐cause mortality in patients with CVD. Infection with influenza leads to a systemic inflammatory and thrombogenic response in the host body, which further causes destabilization of atherosclerotic plaques. Influenza vaccination has been shown to be protective ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 71 publications
1
22
1
Order By: Relevance
“…In other words, PWD were better protected through their or their caretakers’ actions. The tendency for PWD to get vaccinated in this study is consistent with other studies that found individuals with pre-existing medical conditions were more likely to get a vaccine ( Bhugra et al, 2021 ). Individuals who have more contact with the healthcare system or who perceive themselves to be at a higher risk of severe illness from influenza infection may therefore be more likely to receive the vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, PWD were better protected through their or their caretakers’ actions. The tendency for PWD to get vaccinated in this study is consistent with other studies that found individuals with pre-existing medical conditions were more likely to get a vaccine ( Bhugra et al, 2021 ). Individuals who have more contact with the healthcare system or who perceive themselves to be at a higher risk of severe illness from influenza infection may therefore be more likely to receive the vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…The positive connections existed also in non-medics but were weaker. This indicates that all these vaccine cognitions should be enhanced because they capture the most relevant factors in the 4C (confidence, convenience, complacency, calculation) model of vaccine hesitancy [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathologies associated with how influenza viral infection leads to cardiovascular dysfunction are summarized in [ Table 3 ]. [ 66 ],[ 67 ],[ 68 ] The CDC reports people with heart disease or those with a past medical history of a stroke are at higher risk for developing serious flu complications. [ 1 ] Kwong et al .…”
Section: Resultsmentioning
confidence: 99%
“…[ 73 ],[ 74 ] This inflammatory reaction occurs in the coronary bed and atherosclerotic plaques leading to endothelial dysfunction, vasoconstriction, platelet activation, and dysregulation of the coagulation system. [ 68 ] Along with those effects, the brain increases sympathetic activity and metabolic demand. Changes in circulatory volume and vascular tone cause plaque destabilization, increasing the risk for acute myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%